Maslahah’s role as an instrument for revival of ijtihad - Hayatullah Laluddin, (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2015)
Islam presents a comprehensive system of life based on divine guidance. Its dynamism is due its general principles through which solutions for any conceivable situation could be sought. This is in line with the signification of the Quranic verse: “We have not neglected in the record a thing . . .” This necessitates the adoption of an adequate methodology for the derivation of rulings from revealed source. A strict literal approach in understanding of the revealed text would not facilitate solutions for new issues due to the limitation of the text. Thus, maslahah, as a method of interpretation of revealed guidance can play a crucial role in providing solutions for new issues of legal and civilizational nature. Therefore, this article attempts to examine the instrumental role of maslahah in revitalization of Islamic thought. It also highlights the necessity for reviving ijtihad through which stagnation from intellectual spheres of Muslim world could be removed. Maslahah in this context provides an effective instrument for the purpose, hence, can play significant role in restoring originality and dynamism to Islamic thought.